2012
DOI: 10.1039/c2em10545d
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and allergenic fungal spores of the Karachi environment and their correlation with meteorological factors

Abstract: Airborne fungal spores are well known to cause respiratory allergic diseases particularly bronchial asthma, allergic rhinitis, rhino-conjunctivitis and allergic broncho-pulmonary aspergillosis in both adults and children. In order to monitor and analyze airborne fungal flora of the Karachi environment, an aeromycological study was conducted using a Burkard 7-Day Recording Volumetric Spore Trap from January to December 2010. The data recorded from the Spore Trap was further analyzed for percent catch determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…In Turkey, both Alternaria and Cladosporium were significantly and positively correlated with temperature and humidity (Erkara et al, 2009). Our results showed similar trends with studies that have been conducted in countries with similar environment like Qatar, Hasnain et al, (2012) demonstrated that the occurrence of Alternaria spores is negatively and significantly correlated to temperature and Hameed et al, (2007) mentioned a negative insignificant correlation with relative humidity. Çolakoglu (1996) and Nourian et al (2007) found that the concentration of Cladosporium spores increased significantly as the temperature decreased which is in support to our findings.…”
Section: Fungal Species Fluctuation Versus Climatic Factorsupporting
confidence: 81%
See 2 more Smart Citations
“…In Turkey, both Alternaria and Cladosporium were significantly and positively correlated with temperature and humidity (Erkara et al, 2009). Our results showed similar trends with studies that have been conducted in countries with similar environment like Qatar, Hasnain et al, (2012) demonstrated that the occurrence of Alternaria spores is negatively and significantly correlated to temperature and Hameed et al, (2007) mentioned a negative insignificant correlation with relative humidity. Çolakoglu (1996) and Nourian et al (2007) found that the concentration of Cladosporium spores increased significantly as the temperature decreased which is in support to our findings.…”
Section: Fungal Species Fluctuation Versus Climatic Factorsupporting
confidence: 81%
“…(Figure.2). Similar to our results, Hasnain et al (2012) found that the concentration of several fungal spore counts to be significantly and negatively correlated with temperature, though a positive and insignificant correlation was Pepeljnjak, 2006). Based on our statistical correlation analysis between weather data and fungal aerospors, the temperature might have the greatest influence on the dynamics of airborne fungal spores, a fact that have been highlighted by many authors, among those: (Stepalska & Wołek, 2005;Sousa et al, 2008;Grinn-Gofron, 2010;Grinn-Gofroń, & Bosiacka, 2015).…”
Section: Fungal Species Fluctuation Versus Climatic Factorsupporting
confidence: 79%
See 1 more Smart Citation
“…To further evaluate fungal spore number concentrations, we synthesised observations of long-term (those with at least a full annual cycle) fungal spore number concentrations from the literature (Ho et al, 2005;Sousa et al, 2009;GrinnGofron et al, 2011;Herrero et al, 2006;Lim et al, 1998;Henriquez et al, 2001;Hasnain et al, 2012). Observations are typically made using 7-day spore traps and microscopic identification and counting techniques; these methods are inherently uncertain and subject to operator error.…”
Section: Pbap Observationsmentioning
confidence: 99%
“…Out of these, four species belong to the genus Aspergillus. Earlier research work also revealed the presence of these species in indoor environment [22][23][24][25][26]. Many of the indoor fungi cause indoor microbial pollution and also known to produce mycotoxins.…”
Section: Discussionmentioning
confidence: 99%